Rate of Land Use Conversion to Mining and Implications for Carbon Stocks - Amelya Nur Allisa; Christia Meidiana; Fauzul Rizal Sutikno (Pusbindiklatren Bappenas, 2025)
Global warming, driven by escalating atmospheric carbon dioxide CO₂ concentrations, represents a critical threat to global climate stability and exacerbates extreme weather events. Indonesia, particularly East Kalimantan and its capital, Samarinda City, serves as a significant contributor to these emissions due to intensive land-use and land-cover changes (LULCC), primarily characterized by deforestation and the rapid expansion of coal mining. The primary objective of this study is to explicitly quantify the rate of land-use conversion and evaluate its direct implications for terrestrial carbon stocks in Samarinda City over a decadal period from 2014 to 2024. To achieve this, the research utilizes high-resolution Landsat 8 OLI/TIRS satellite imagery processed through Geographic Information Systems (GIS) and Google Earth Engine for temporal change detection. Carbon stocks were quantified using the ICLEI carbon calculator by integrating spatial transition data with biomass-based carbon indices. Key findings reveal a substantial decline in the city's total carbon stock, falling from 1,630,212.52 tons in 2014 to 1,442,812.07 tons in 2024. This depletion is fundamentally linked to a 65.22% expansion of mining areas. The results underscore the urgent need for integrating strategic zoning within the Regional Spatial Plan (RTRW) and adopting advanced carbon mineralization technologies to mitigate further carbon stock loss.